Rare case of transverse testicular ectopia – Case report and review of literature. (2017) - Raj, Vinod; Redkar, Rajeev; Krishna, Swathi; Tewari, Shruti
Highlights: Transverse testicular ectopia is a rare condition with just around 100 cases described in the literature. Most of these are diagnosed on surgical exploration. Short review of literature on its etiology and management. We provide a modification of algorithm for its management highlighting the need of diagnostic laparoscopy. Abstract: This case report has been reported in line with the SCARE criteria; Consensus-based surgical case report guidelines of International Journal of Surgery 2016. Introduction: Transverse Testicular Ectopia (TTE) is a rare condition which manifests with unilateral undescended testis and contralateral hernia. Till now around 100 cases have been described in the literature. The management depends on the anatomy of the vas, vessels and testis found on surgical exploration. An algorithm exists for its management and we propose a modified algorithm for management of TTE. Case presentation: Five year male presented with complaints of unilateral undescended testis on the right and hernia on the left. Clinically the right testis was impalpable and left testis palpable in the left hemiscrotum and fluid hernia on the same side. Discussion: Transverse testicular ectopia is a rare condition presenting with UDT and contralateral inguinal hernia. Although more than 100 cases have been described in the literature so far, those managed with a transeptal contralateral orchidopexy are two cases to the best of our knowledge. TTE was first described by Von Lenhossek in 1886. The mean age of presentation is around 4 years and most of the cases are diagnosed on surgical exploration. The management of TTE remains controversial even though an algorithm has been described for its management due to its varied presenting scenarios. Conclusion: TTE is a rare condition which requires high index of suspicion for diagnosis preoperatively. Whenever suspected we recommend an USG and/or MRI prior to diagnostic laparoscopy and proceed with orchidopexy. Diagnostic laparoscopy is both helpful in diagnosis and management. Transeptal contralateral orchidopexy gives good tension free fixation of testes in the scrotum.